2015
DOI: 10.3109/09546634.2015.1049972
|View full text |Cite
|
Sign up to set email alerts
|

Patient reported health outcomes and non-adherence in psoriasis patients receiving adalimumab or ustekinumab for moderate to severe plaque psoriasis

Abstract: UST versus ADA PsO bio-naïve patients reported higher clearing rates, better DLQI, and lower activity impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
2
9
1
Order By: Relevance
“…In line with our study, the medication adherence rate ranged from 33% to 78% in a study by Gorin et al, and one-third of the patients discontinued their regular treatment due to forgetfulness to use their medicine, high cost of drugs, long duration of medical treatment, and other medical problems (25). On the other hand, Joeteck et al reported a medication adherence rate of 56.5%, which is consistent with the present study (26).…”
Section: Discussionsupporting
confidence: 82%
“…In line with our study, the medication adherence rate ranged from 33% to 78% in a study by Gorin et al, and one-third of the patients discontinued their regular treatment due to forgetfulness to use their medicine, high cost of drugs, long duration of medical treatment, and other medical problems (25). On the other hand, Joeteck et al reported a medication adherence rate of 56.5%, which is consistent with the present study (26).…”
Section: Discussionsupporting
confidence: 82%
“…In our cohort of 247 patients treated with adalimumab, etanercept, or ustekinumab for more than 350 days, only 15 patients (6.1%) had an MPR <80%, indicating nonadherence. These results are in agreement with self-reported patient adherence to biologics [13] but in stark contrast to the data of Goren et al [19], who recorded that 11.8 and 32.5% of patients were nonadherent to ustekinumab and adalimumab, respectively. In patients with rheumatoid arthritis the proportion of adherent patients has been reported to be as low as 11% (reviewed by De Vera et al [3]).…”
Section: Discussioncontrasting
confidence: 57%
“…4). Other authors have also reported lower adherence to etanercept than to ustekinumab or adalimumab [19,25]. …”
Section: Discussionmentioning
confidence: 99%
“…This is confirmed by the results obtained during analysis of patients' replies to the A14 Adherence Scale, where the item ‘My previous treatments were not efficient’ was significantly correlated with adherence. Our data collection was not designed to identify the impact of the active ingredient on adherence and can therefore not add information to the medication‐related adherence aspects reported elsewhere …”
Section: Discussionmentioning
confidence: 99%
“…Our data collection was not designed to identify the impact of the active ingredient on adherence and can therefore not add information to the medication-related adherence aspects reported elsewhere. 11,16,23,[25][26][27] Being asked for the main reason for non-adherence, dermatologists primarily name the patients' fear of adverse reactions. This thinking precipitates in their communication with the patient as the respondents strongly agree (12 of 13 dermatologists) that provision of enough information regarding possible risks and adverse effects enhances the patient's therapy adherence (see Table 4).…”
Section: Discussionmentioning
confidence: 99%